Estudo das propriedades estruturais e eletrônicas do arseneto de boro e análogos - Barboza, Elisangela da Silva (2023)
In this work we theoretically investigate structural and electronic properties of cubic boron arsenide crystal (BAs) and analogues through calculations ab initio based on density functional theory (DFT), in order to understand and relate their physical properties . In our study BAs is subjected to hydrostatic pressures of 10%, 20% and 30% to understand how the normal electronic state changes under external pressure. Furthermore, we compared our result for compressed 30% BAs with those obtained for GaAs and InAs at ambient pressure, showing good qualitative agreement between these three different systems. In this work, all our density functional theory calculations were implemented using the quantum espresso (Q.E) computational package. We show that the shear energy and the number of ⃗k points k play an important role in the result of our calculations. When analyzing the convergence of the total energy as a function of the network parameter, it is verified that the network parameter is underestimated (overestimated) within the LDA approximation (GGA). Using the LDA and GGA approximations, our results for the bulk modulus are in good agreement with existing calculations in the literature. Furthermore, we studied the electronic properties of BAs, GaAs and InAs systems at ambient pressure. In line with previous studies, the results obtained for the band structure show that BAs has an indirect gap between the point Γ−X with a value close to 1.15 eV, while GaAs has a direct gap of 0,67 eV and InAs is a semi-metal. Pressurized BAs showed clear changes in electronic properties, particularly at high pressures, where its band gap is reduced. In this particular regime, the electronic structure of the BAs shows the appearance of the semi-metallic state when increasing the pressure.